A Systematic Approach for Designing a Neural Network Using Existing Algorithms to Detect H2, CH4, and CO Gases - Sanju Meetei, Maibam; Chamuah, Anil; Yabom, Yabom; Dinamani Singh, Aheibam (International Journal of Engineering and Technology, 2018)
A neural network has different parameters like weight, bias, activation function and hidden layers. Different algorithms are applied to set the parameters and various normalization techniques applied to the input data also differs the performance of the network. So, it is very important for a designer to design the network by considering the above variables like the number of layers, different normalization techniques, different activation functions and different algorithms. It is very important to optimize all these parameters for better performance.Â Â